Kindergarten and school : compared curriculums - Wannack, Evelyne (Swiss Journal of Educational Research, 2003)
This article examines the pedagogical purpose of kindergarten and primary school comparing the curricula of the canton Berne. Three questions direct the qualitative content analysis:1. What pedagogical and didactic principles are characteristic for kindergarten?2. Where do we find tendencies of similarity and difference between kindergarten and primary school?3. Which areas provide opportunities for educational innovation?A qualitative content analysis reveals two different leitmotifs: for kindergarten it is the leit-motif “development” and for school it is “learning”. Despite the different leitmotifs there are tendencies towards similarity, especially for the didactic principle of individualization. This area provides manifold possibilities for the further development of educational concepts.